Conclusions around theories of change in reality - Koleros, Andrew; Adrien, Marie-Hélène; Tyrrell, Tony (Theories of Change in Reality, 2024)
This book sets out the responses from a group of international practit ioners and experts to three questions posed by the editors around how they are using theories of change in their work, what they have found to be the limits of their use, and what further adaptations they feel are needed so that theories of change remain relevant and useful in th e future. The responses we received are, given the diversity of the co ntributors, understandably diverse with reference to perspective, emph asis, and the context within which theories of change are used. Broadl y, their perspectives indicate that theories of change have long repre sented a valuable approach in both programme planning as well as in ev aluation design and practice; however, the authors also make clear tha t theories of change are often misunderstood and misused. In particula r, the authors draw attention to the use of theories of change as a st atic product rather than an iterative, inclusive process that recognis es the centrality of multiple stakeholder perspectives in evaluation d esign and practice. The authors also highlight the challenges involved in the application of theories of change in contexts defined by heigh tened complexity.